2021
DOI: 10.1371/journal.pone.0257736
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and health impacts of fall armyworm in Ethiopia

Abstract: Since 2016, fall armyworm (FAW) has threatened sub-Saharan ‘Africa’s fragile food systems and economic performance. Yet, there is limited evidence on this transboundary pest’s economic and food security impacts in the region. Additionally, the health and environmental consequences of the insecticides being used to control FAW have not been studied. This paper presents evidence on the impacts of FAW on maize production, food security, and human and environmental health. We use a combination of an agroecology-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…Against the background variance caused by differences in soils and plot management, we were unable to detect any significant effect of S. frugiperda infestation, or leaf damage on yield. These results are in stark contrast to many other reports from the region, including from Malawi and Zambia, that have tended to suggest very high levels of yield loss caused by S. frugiperda ( Kansiime et al 2019 , De Groote et al 2020 , Kassie et al 2020 , Abro et al 2021 , Tambo et al 2021 , Kwasi et al 2022 , Makale et al 2022 ). How can we reconcile these very different findings?…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Against the background variance caused by differences in soils and plot management, we were unable to detect any significant effect of S. frugiperda infestation, or leaf damage on yield. These results are in stark contrast to many other reports from the region, including from Malawi and Zambia, that have tended to suggest very high levels of yield loss caused by S. frugiperda ( Kansiime et al 2019 , De Groote et al 2020 , Kassie et al 2020 , Abro et al 2021 , Tambo et al 2021 , Kwasi et al 2022 , Makale et al 2022 ). How can we reconcile these very different findings?…”
Section: Discussioncontrasting
confidence: 99%
“…Since its arrival in sub-Saharan Africa, there have been a number of reports concerning the impacts of S. frugiperda . Most have suggested that these impacts are substantial ( Kansiime et al 2019 , De Groote et al 2020 , Kassie et al 2020 , Abro et al 2021 , Tambo et al 2021 , Kwasi et al 2022 , Makale et al 2022 ). For example, based on household surveys, Tambo et al (2021) reported that severe infestations caused a 44% reduction in household income and a 17% increased likelihood of experiencing hunger in Zimbabwe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in Africa highlight the economic importance of the FAW. In Ethiopia, the pest causes an average annual loss of 36% in maize production, reducing yield by 0.225 million tonnes of grain between 2017 and 2019 (Abro et al 2021). In Kenya, FAW causes losses of about a third of the annual maize production, estimated at about 1 million tonnes, with large variations among regions (De Groote et al 2020).…”
Section: Host Range Damage To Crops and Economicmentioning
confidence: 99%
“…Because of its edacious feeding habits, diverse host range, ability to fly longer distances, capacity to multiply fast, and short life cycle with no diapause growth phase, it has been difficult to control, manage or eradicate [3,5,6]. Since its arrival on the African Continent, between 11-54% of maize production is reported to be lost annually [7,8]. In Zambia, the pest was first detected in December 2016 on the Copperbelt Province, about 400km northwest of Lusaka, and has since spread to all the ten provinces of the country [9], with the infestation as high as 40% in some cases and with farm-level yield losses of more than 35% [10].…”
Section: Introductionmentioning
confidence: 99%